Application of Bayes' Theorem Method to Diagnose Miscarriage in Pregnant Women - Siagian, Edward Robinson (Pascal: Journal of Computer Science and Informatics, 2024)
The expert system for diagnosing the causes of miscarriage in pregnant women is an expert system designed as a tool to diagnose the type of food that causes miscarriage. Computer programs intended as a provider of tools in solving problems in certain areas of specialization such as miscarriage problems in pregnant women. This knowledge is obtained from various sources including books and the internet related to the causes of miscarriages. The knowledge base is arranged in such a way into a database with several tables of food types and tables of effects to facilitate the performance of the system in drawing conclusions in this expert system using Bayes' theorem. This expert system will display a selection of symptoms that can be selected by the user, where each effect selection will read the user to the next effect choice until the final result is obtained. In the final result, the expert system will display a selection of user effects, types of foods that cause miscarriage, and solutions.